Effect of surface-etched modification on halloysite nanotubes (HNTs) for polysulfone mixed matrix membrane in CO2/CH4 separation - Jafa, J.; S. M., Anissuzaman; Chiam, C. K.; Bolong, N.; A. R., Razali; A. F., Ismail; N. M., Ismail (IOP Publishing, 2020)
Mixed matrix membranes (MMMs) were fabricated from a 25 wt% of polysulfone (PSf) with halloysite nanotubes (HNTs) selected as the inorganic filler. The incorporation of 1 wt% to 5 wt% of HNTs in the membrane is promising in improving the performance of the membrane for gas separation due to its barrier properties. HNTs was modified by surface-etched method before it is embedded into the membrane in order to reduce the interfacial defects as well as the agglomeration in the membrane. This study further investigated the improvement of the polymer-clay interface interaction, characterize the functional groups, structure and surface area of the newly modified clay and also mechanical properties of the membrane. From the FTIR spectra, it can be seen that the functional group of surface-etched HNTs reduced in intensities compared to the unmodified HNTs. There are no distinct changes in XRD pattern for both unmodified and modified HNTs and tensile strength shows an increment in MMMs embedded with modified clay compared to unmodified clays. The incorporation of surface-etched HNTs was able to improve the membrane properties to a desired membrane that can be applied in the CO2 and CH4 separation.